PENGARUH MEDIA SOSIAL DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN SAYUR HIDROPONIK (STUDI KASUS PADA CENTRAL HIDROPONIK KOTA BENGKULU) - Weri Antika; Yulius Wahyu Setiadi ((JEMS) Jurnal Entrepreneur dan Manajemen Sains, 2021)
One of the vegetable products that are currently in demand by consumers is hydroponic vegetables.Â  Therefore, researcher is interested in conducting a study entitled the effect of social media and brand image on hydraulic vegetable purchase decisions (Case Study on Central Hydroponics, Bengkulu City). This study aimed to ascertain or find out the effect of social media and brand image on purchasing decisions of hydroponic vegetables (a case study at the Central Hydroponics of Bengkulu City). This study employed a quantitative descriptive research method by transforming Likert scale data into interval scale data.The population in this study were all consumers of Central Hidroponik Bengkulu who visited or made transactions and took samples using the accidental sampling method.Based on the results of multiple linear regression, the form of regression equation is Y = 5.145 + 0.669 (X_1) + 0.260 (X_2). The study results and hypotheses indicate that Social Media (sig Î± = 0.000 <0.05), Brand Image (sig Î± = 0.002 <0.05).Simultaneously and significantly predisposed on purchasing decisions. Partially, the Social Media and Brand Image variables have a significant effect on purchasing decisions and it is better if the leaders of Bengkulu City Central Hydroponics can continue to maintain their existence and increase sales more effectively.Keywords: Social Media, Brand Image, And Purchase Decisions.